Contemporary Strategies for Clinical Chemoprevention of Localized Prostate Cancer - Nagi B Kumar PhD (Cancer Control, 2024)
Prostate cancer (PCa) is the most common cancer among men in the United States and the second leading cause of cancer-related deaths. Metastatic castration-resistant PCa is still a fatal disease. On the other hand, between 2016 and 2020, about 70% of PCa cases were diagnosed at a localized stage. Evolving data demonstrates that men with low-grade cancers treated with definitive therapies may now be exposed to morbidities of overtreatment and poor quality of life, with little or no benefit in terms of cancer specific mortality. Active surveillance (AS) is thus the recommended management strategy for men with low-grade disease. Although this subgroup of men have reported anxiety during the AS period, they account to be highly motivated to make positive lifestyle changes to further reduce their risk of PCa progression, underscoring the urgent need to identify novel strategies for preventing progression of localized PCa to metastatic disease through pharmacologic means, an approach termed chemoprevention. Although several promising agents and approaches have been examined over the past 2 decades, currently, there are several limitations in the approach used to systematically examine agents for chemoprevention targeting men on AS. The goal of this review is to summarize the current agents and approaches evaluated, targeting men on AS, recognize the gaps, and identify a contemporary and comprehensive path forward. Results of these studies may inform the development of phase III clinical trials and ultimately provide a strategy for clinical chemoprevention in men on AS, for whom, currently, there are no options for reducing the risk of progression to metastatic disease.